Sistem Otomatis Pembuatan Nutrisi Ideal untuk Tanaman Pakcoy Menggunakan kendali Logika Fuzzy - Aditya Malik; Rodi Hartono (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2021)
Basically, especially in Indonesia, on average, hydroponic plantations still use a manual sistem, including in regulating nutrition, farmers still use a manual sistem in their settings. It takes a lot of time to do the manual feeding, the farmer must first provide water for each nutrient reservoir, then after that the farmer must give fertilizer or nutrients A and B to mix with water and stir. The purpose of this research is to design and implement a sistem of checking and regulating nutrient composition with fuzzy logic method to obtain and maintain ideal nutritional conditions for hydroponic pakcoy plants. In this research, the method used is the fuzzy method, the nature of the uncertainty that often arises will be resolved. By creating 19 input membership sets and 19 output membership sets that have been created by taking data for nutrient concentration values ​​reaching the set point of 1050-1400 ppm, the sistem will be able to create and maintain nutrient concentration values ​​in the ideal range. From the sistem testing carried out, it was concluded that the most addition of nutrients A and B was 5100 mL with a time of 17 minutes in the state of the maximum nutrient container, and the addition of nutrients A and B at least 300 mL with a time of 1 minute in the state of the maximum nutrient container. Keyword :Fuzzy, concentration value, nutrition, pakcoy, PPM